2022
DOI: 10.1001/jamanetworkopen.2022.41144
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Accessibility of COVID-19 Test to Treat Sites by Race, Ethnicity, Age, and Rurality

Abstract: This cross-sectional study explores geographic disparities in antiviral access by quantifying the accessibility of COVID-19 Test to Treat sites for subpopulations by race, ethnicity, age, and rurality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Given the importance of equitable testing access and the compounding issue that those with less access to pharmacies are often the individuals at greatest risk of severe COVID-19 [ 30 ], government-funded Test-to-Treat programs were developed in 2022 as a rapid means to provide testing, prescriptions, and medications to underserved populations [ 29 ]. Although this was productive, many rural communities remain without access [ 29 , 31 ]. Recent efforts by the National Institutes of Health, the Administration for Strategic Preparedness and Response, and the CDC to deploy home-based Test-to-Treat programs hold significant promise to overcome geographical barriers [ 32 , 33 ], but testing hesitancy may pose an upstream challenge for broader utilization of these initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of equitable testing access and the compounding issue that those with less access to pharmacies are often the individuals at greatest risk of severe COVID-19 [ 30 ], government-funded Test-to-Treat programs were developed in 2022 as a rapid means to provide testing, prescriptions, and medications to underserved populations [ 29 ]. Although this was productive, many rural communities remain without access [ 29 , 31 ]. Recent efforts by the National Institutes of Health, the Administration for Strategic Preparedness and Response, and the CDC to deploy home-based Test-to-Treat programs hold significant promise to overcome geographical barriers [ 32 , 33 ], but testing hesitancy may pose an upstream challenge for broader utilization of these initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals from racial and ethnic minority groups are less likely to have access to novel and high-cost medications and are less likely to receive evidence-based antimicrobials [21,45]. This includes inclusion in clinical trials for novel therapies [46 ▪▪ ,47]. Barriers to care also lead to increased use of nonprescription antibiotics, which itself has been associated with higher community rates of AMR [48].…”
Section: Current Disparities: Antimicrobial Prescribing Patterns and ...mentioning
confidence: 99%
“…Stewardship campaigns should be as diverse and inclusive as possible, in order to benefit groups who have been historically excluded, reduce inappropriate antimicrobial use in these populations, and support pharmacoequity in clinical research from bench to bedside. Implementation of broad programs without regard for the specific communities experiencing disproportionate disease prevalence or lack of access to treatment can lead to well intentioned initiatives missing the mark [47,63]. Recommendations to optimize programs designed to address inequities include advocacy for increased public awareness and prioritization of key multisector stakeholders from in decision-making [64] (Fig.…”
Section: Increased Public Awareness About Antimicrobial Resistance An...mentioning
confidence: 99%
“…Visitor restrictions observed early in the pandemic, along with the need to travel away from their community of support, may have led rural patients to hesitate in seeking care ( Henning-Smith, 2020 ). Recent studies have reported that rural patients had to travel a median time of 69.6 min to a test and treatment site compared to urban populations, where the median travel time was 11 min ( Khazanchi et al, 2022 ). Since these sites provide access to treatments such as nirmatrelvir-ritonavir and molnupiravir, which need to be initiated within 5 days of symptom onset for maximum efficacy, long travel distances to treatment centers may be a barrier for patients residing in rural areas.…”
Section: Sars-cov-2 Rural Health Disparitiesmentioning
confidence: 99%